Accelerated detection of mycolactone production and response to antibiotic treatment in a mouse model of Mycobacterium ulcerans disease. - Paul J Converse; Yalan Xing; Ki Hyun Kim; Sandeep Tyagi; Si-Yang Li; Deepak V Almeida; Eric L Nuermberger; Jacques H Grosset; Yoshito Kishi (Public Library of Science (PLoS), 2014)
Diagnosis of the neglected tropical disease, Buruli ulcer, can be made by acid-fast smear microscopy, specimen culture on mycobacterial growth media, polymerase chain reaction (PCR), and/or histopathology. All have drawbacks, including non-specificity and requirements for prolonged culture at 32°C, relatively sophisticated laboratory facilities, and expertise, respectively. The causative organism, Mycobacterium ulcerans, produces a unique toxin, mycolactone A/B (ML) that can be detected by thin layer chromatography (TLC) or mass spectrometric analysis. Detection by the latter technique requires sophisticated facilities. TLC is relatively simple but can be complicated by the presence of other lipids in the specimen. A method using a boronate-assisted fluorogenic chemosensor in TLC can overcome this challenge by selectively detecting ML when visualized with UV light. This report describes modifications in the fluorescent TLC (F-TLC) procedure and its application to the mouse footpad model of M. ulcerans disease to determine the kinetics of mycolactone production and its correlation with footpad swelling and the number of colony forming units in the footpad. The response of all three parameters to treatment with the current standard regimen of rifampin (RIF) and streptomycin (STR) or a proposed oral regimen of RIF and clarithromycin (CLR) was also assessed. ML was detectable before the onset of footpad swelling when there were <10(5) CFU per footpad. Swelling occurred when there were >10(5) CFU per footpad. Mycolactone concentrations increased as swelling increased whereas CFU levels reached a plateau. Treatment with either RIF+STR or RIF+CLR resulted in comparable reductions of mycolactone, footpad swelling, and CFU burden. Storage in absolute ethanol appears critical to successful detection of ML in footpads and would be practical for storage of clinical samples. F-TLC may offer a new tool for confirmation of suspected clinical lesions and be more specific than smear microscopy, much faster than culture, and simpler than PCR.